2022
DOI: 10.3390/ma15030992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Fly Ash Content on the Fresh and Hardened Properties of Alkali-Activated Slag Pastes with Admixtures

Abstract: A study on the influence of the inclusion of slag or fly ash and five types of superplasticizers on the fresh and hardened properties of alkali-activated cements is presented. Three alkali-activated slag formulations with different fly ash content (0, 15, and 30%) in the presence of five admixtures (vinyl copolymer, melamine, and three polycarboxylates with different chain lengths) were assessed for fluidity control and setting adjustment without loss of mechanical properties. Solid sodium metasilicate was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Hence, another innovative route has been suggested. For example, steel waste could be utilized as an alkali-activated material in the production of greener construction materials [ 73 , 74 , 75 ].…”
Section: Steel Waste Managementmentioning
confidence: 99%
“…Hence, another innovative route has been suggested. For example, steel waste could be utilized as an alkali-activated material in the production of greener construction materials [ 73 , 74 , 75 ].…”
Section: Steel Waste Managementmentioning
confidence: 99%
“…In addition, calcium in fly ash can promote the formation of C-S-H gels, and fly ash with high calcium content is more conducive to improving the strength of geopolymer [ 12 ], but the inadequacy of calcium fraction on the development of three-dimensional mesh structure of geopolymer restricts the application of high-calcium fly ash [ 13 ]. Studies have shown that geopolymers with a high fly ash content tend to have better flowability but reduce the reaction rate and compressive strength [ 14 ]. Fly ash geopolymer can significantly improve the overall strength of the soil in the application of cured soil [ 15 ], but it has a slow reaction rate and low hardening strength, which make it difficult to achieve the bearing capacity requirements if it is directly applied in road subgrade repair.…”
Section: Introductionmentioning
confidence: 99%